Validitas Pengembangan Modul Pembelajaran Biologi Berorientasi Mind map dengan Variasi Tebak Kata untuk Peserta Didik Kelas VIII SMP - Darmanella Dian Eka Wati; Ratih Komala Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Teacher’s success in implementing learning depends on the insight, knowledge, understanding and creativity level in managing teaching materials. One form to process subject matter is by using the module. Module oriented Mind map (MM) equipped with Words Guess game will become more interesting and can develop students’ interest and creativity. The development of this module must pass the validity test stage by the validator before it is used in the learning process. The purpose of this research is to know the developed validity of Biology Learning Module, which orients Mind map (MM) equipped with a Words Guess game in class VIII SMP. This research is a development research (Research and Development) using 4-D model consisting of 4 stages of define, design, develop, and disseminate. By far, this research only reaches the development stage which is at validity test phase. Based on validity test results by 4 validates indicate that developed learning module Biology oriented Mind map with Words Guess variation is a very good category to be used in the learning process.